1991
DOI: 10.1271/bbb1961.55.2349
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Nucleotide Sequencing, and Expression in Escherichia coli of a Lipase and Its Activator Genes from Pseudomonas sp. KWI-56.

Abstract: A lipase gene (lip) and its activator gene (act) on a 2.9 kb BglII-EcoRI fragment from Pseudomonas sp. KWI-56 were cloned in Escherichia coli using pUC19 as a vector plasmid. From the sequencing results, the open reading frames of the lip and the act were found to contain 1092 and 1032 nucleotides, respectively. The act existed downstream of the lip with the same orientation. When the lip was expressed in E. coli using the lac promoter on the pUC plasmid vector, the lipase activity of E. coli carrying both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 0 publications
2
28
0
Order By: Relevance
“…ORF D4225 shows 21.8% identity in a 326 aa overlap with triacylglycerase lipase from Pseudomonas sp. (Iizumi et al, 1991). ORF D4241 has 28.9% identity in a 363 aa overlap with E. coli deoxyribodipyrimidine photolyase (Dorrell et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…ORF D4225 shows 21.8% identity in a 326 aa overlap with triacylglycerase lipase from Pseudomonas sp. (Iizumi et al, 1991). ORF D4241 has 28.9% identity in a 363 aa overlap with E. coli deoxyribodipyrimidine photolyase (Dorrell et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Pseudomonas glumae was also found to be efficient in a system of washing model (Iizumi et al, 1991, Jorgesen et al, 1991. Span 80 was chosen for the following studies as it showed the highest percentage of oil removal in the presence of lipase.…”
Section: Resultsmentioning
confidence: 99%
“…fluorescens SIK W1 [23], B52 [24], and Pseudomonas sp. LS107d2 [25] [13], and 109 [15]. Class III lipases share two features: (a) the precursor protein possesses a signal peptide and (b) the supplemental gene downstream of the lipase gene is essential to express lipase activity in E. coli.…”
Section: Discussionmentioning
confidence: 99%